1997
DOI: 10.1111/j.1399-6576.1997.tb04837.x
|View full text |Cite
|
Sign up to set email alerts
|

Can training improve the results with infrared tympanic thermometers?

Abstract: Training had little effect on the accuracy of the measurements. According to our results, ITT is often unreliable and should be used with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
6
25
0
Order By: Relevance
“…Second, Amoateng-Adjepong et al (11) reported greater variability of readings when tympanic measurements were performed by nurses in routine clinical practice. Before commencement of the current study, inservice education was undertaken, although "training" may have little impact on the performance of tympanic temperature measurement (56). Third, no specific detailed examination of the ears was undertaken during the study to rule out local factors in the ear (e.g., cerumen, perforation) that may have influenced tympanic temperature measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Amoateng-Adjepong et al (11) reported greater variability of readings when tympanic measurements were performed by nurses in routine clinical practice. Before commencement of the current study, inservice education was undertaken, although "training" may have little impact on the performance of tympanic temperature measurement (56). Third, no specific detailed examination of the ears was undertaken during the study to rule out local factors in the ear (e.g., cerumen, perforation) that may have influenced tympanic temperature measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Core temperature can also be assessed using tympanic thermometers. However, this method is not available in every intensive care unit as it is time-consuming and requires trained operators [5,8,9]. Moreover, it has been shown that tympanic thermometry is not reliable in critically ill patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Rectal temperature is in general higher than at other places, [31,32] due to the low blood flow and high isolation of the area, leading to a low heat loss. [33] Also, the heat-producing activity of micro-organisms in faeces influences the reading. [34] In line with previous research, [10] it is also obvious that the difference between rectal and ear temperatures differs between individuals, strengthening that exact…”
Section: Discussionmentioning
confidence: 99%